Sosialisasi Bijak Bermedia Sosial sebagai Upaya Mengantisipasi Stres pada Remaja di Masa Pandemi COVID-19 - Dewi Hambar Sari; Ulva Melinia Saputri (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic has an impact on the physical health aspect and the psychology of the community, especially the emotions to experience stress and anxiety. This psychological impact is not only experienced by groups who are vulnerable to COVID-19 but also teenagers. The information circulating on social media about COVID-19, both factual information or hoaxes, triggers stress and anxiety among teenagers. This community service is carried out to provide education to teenagers on how to be wiser using social media so that they can anticipate anxiety and stress as a result of using social media. This activity was carried out for high school teenagers who are members of the youth organization in Ngudi, Blora, by providing counselling on two subjects, namely 1) the SIFT method to anticipate hoaxes circulating on social media, 2) how to anticipate stress as a result of using social media. The results of this activity are participants' understanding of how to behave and act on information obtained from social media, as well as participants' understanding of ways to anticipate stress during the COVID-19 pandemic. In general, the participants were enthusiastic about participating in this activity and get benefits.